PENGARUH KOMPENSASI, KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (Universitas Mahendradatta, 2022)
Abstract - This study aims to examine and analyze the effect of compensation,leadership and work discipline on employee performance. Data was collected bydistributing questionnaires to 46 respondents and analyzed using the SEM-PLS method.The results of this study indicate that work discipline has an effect on employeeperformance but there is no effect of compensation and leadership on employeeperformance.